Role of robotic arm assistance in computed tomography guided bone biopsy - Mehta, Natasha N.; Mehta, Nikit; Gorde, Nitin (International Journal of Research in Medical Sciences, 2019)
Background: Use of robotic assistance technique has significant benefits over conventional techniques. The present study looks at the recent technological developments in image guidance for bone biopsy procedures. Methods: Patients who were referred to the department of radiodiagnosis, Bharti Hospital and Dot3d scanning center, Sangli, Maharashtra, India from July 2017 till December 2018 with suspected bone lesions were included in the study. These patients underwent robotic arm CT guided bone biopsy of their lesions. Results: In the present study, 47 patients were included. Authors observed that 93.6% had a positive diagnosis based on CT guided bone biopsy. Metastatic lesions were diagnosed in 8 cases. Inflammatory lesions and tuberculosis were other commonly observed diagnosis. Conclusions: Further growth and development of medical imaging devices have allowed more interventional procedures to be performed and more patients to benefit from them. Radiologists needs to develop a thorough understanding of the anatomical structure involved and need to acquire both solid grounding in technology and the practical skills to visualize a nerve structure.